Conventional and biological therapies in atopic dermatitis – a literature review - Włodarczyk-Cybulska, Karolina; Sergiel, Natalia; Maj, Patrycja; Mozer, Piotr; Maternia, Jakub; Lazar, Michał; Kania, Agata; Serwik-Trandasir, Aleksandra; Gonet, Malwina; Miszczyk, Karolina (Journal of Education, Health and Sport, 2023)
Introduction: Atopic dermatitis is a chronic, relapsing disease with a multifactoral etiology. The basic disorder of the atopic dermatitis is the disruption of the epidermal barrier. The family history of atopy is a high risk factor of the development of the disease. The clinical manifestations are heterogeneous and vary depending on patient’s age, disease duration and current disease activity according to the SCORAD scale. Objective: The aim of the review is to analyze the latest information on the characteristics, diagnosis and treatment of atopic dermatitis, including new biological medications. Methods and materials: The sources available in PubMed database have been analyzed using the keywords: „atopic dermatitis”, „epidermal barrier”, „SCORAD index”, „topical treatment”, „biological therapy”, „Janus kinase inhibitors”. Current state of knowledge: Atopic dermatitis is only treated symptomatically. The greatest therapeutic challenge is to reduce the pruritus which significantly impairs the quality of life. Topical corticosteroids may cause local side effects. The most severe cases of the disease require systemic treatment with immunosuppressants. Conclusions: The complex pathogenesis of atopic dermatitis is the object of research. Understanding the immunological mechanisms responsible for the development of the disease allows to introduce new therapeutic options. Previous studies have confirmed the effectiveness of biological medications in reducing disease activity, which is a chance to improve the quality of live of the patients suffering from atopic dermatitis.